2011
DOI: 10.1038/ncb2216
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the myosin-II-responsive focal adhesion proteome reveals a role for β-Pix in negative regulation of focal adhesion maturation

Abstract: Focal adhesions (FAs) undergo myosinII-mediated maturation wherein they grow and change composition to modulate integrin signaling for cell migration, growth and differentiation. To determine how FA composition is modulated by myosinII activity, we performed proteomic analysis of isolated FAs and compared protein abundance in FAs from cells with and without myosinII inhibition. We identified FA 905 proteins, 459 of which changed in FA abundance with myosinII inhibition, defining the myosinII-responsive FA prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

55
602
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 544 publications
(659 citation statements)
references
References 74 publications
(74 reference statements)
55
602
2
Order By: Relevance
“…bPIX regulates formation of protrusions (14,(37)(38)(39), and overexpression of bPIX in fibroblasts and neurons alters the localization of bPIX itself, GIT1, Rac activity, and protrusions from a single leading edge to all around the cell periphery (37,39). Moreover, increased Rac activity in fibroblasts and epithelial cells correlates with multiple peripheral lamellae, or protrusions, and increased random motility (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…bPIX regulates formation of protrusions (14,(37)(38)(39), and overexpression of bPIX in fibroblasts and neurons alters the localization of bPIX itself, GIT1, Rac activity, and protrusions from a single leading edge to all around the cell periphery (37,39). Moreover, increased Rac activity in fibroblasts and epithelial cells correlates with multiple peripheral lamellae, or protrusions, and increased random motility (40).…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that aPix 2 mice have reduced numbers of peripheral T and B cells, and aPix 2 T cells show greatly increased rates of basal and CXCL12-induced migration (12). Although aPIX and bPIX have both been implicated in cytoskeletal dynamics such as migration, focal adhesion, and polarization in other cell types (12)(13)(14)(15), the role of PIX proteins in thymocyte development and functions is unknown.…”
mentioning
confidence: 99%
“…14,15 However, it has become increasingly apparent that, apart from being activated by upstream cues, NMII can also exert influence upon these signaling pathways. 1,7,[16][17][18] For example, NMII can associate with RhoA regulators, and, indeed, inactivating NMII with blebbistatin was reported to activate GEFs that promoted Rac signaling. 18 Recently, we identified a novel positive feedback loop for NMII-dependent RhoA signaling, where junctional NMIIA supports GTP-RhoA at the ZA.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic phase involves the maturation of the adhesion complexes, which is induced by actomyosin-dependent contraction and causes the downregulation of the Rac1 activation pathway (Kuo et al 2011). Increasing local contractile pressure results in the maturation of adhesion sites, which then grow in size (valency regulation).…”
Section: Integrin-mediated Migrationmentioning
confidence: 99%